Isolation and characterization of actinomycetes with in-vitro antagonistic activity against Fusarium oxysporum from rhizosphere of chilli - Jalaluldeen, Anfal Muayad; Sijam, Kamaruzaman; Othman, Radziah; Mior Ahmad, Zainal Abidin (ER Publications, 2014)
This study was carried out to isolate and characterize antagonistic bacteria against wilt causing fungal pathogen i.e. Fusarium oxysporum, from the rhizosphere of chilli plant. Twenty bacterial strains were isolated from the rhizosphere soil samples from healthy chilli plant, collected from different locations of UPM, Serdang, Malaysia. Out of these, seven isolates were found to be antagonistic against the tested fungal pathogen i.e. Fusarium oxysporum, under in-vitro conditions. On the basis of percentage inhibition of radial growth of Fusarium oxysporum, isolate At 5 was found to be the most effect ive antagonistic rhizobacteria against the pathogen. Based on its morphological and biochemical properties along with 16s rRNA sequence analysis, it was identified as a Streptomycetes indiaensis with accession number KJ872546. Average percentage inhibition given by this isolate was 71%,and it was found to producediffusible and volatile antifungal metabolites along with hydrogen cyanide and ammonia. Effect of physiological parameters on the growth and antagonistic behavior of the potential isolates was also examined. The present study, hence, provides a potential biocontrol agent for Fusarium oxysporum, however, field studies of this isolate as soil inoculants in chilli are required in order to establish its actual performance.